Whether to push or pull? Nicotine reduction and non-combusted alternatives - two strategies for reducing smoking and improving public health - Smith, Tracy T. (Prev Med, 2018)
Combustible cigarettes remain the most harmful and addictive tobacco product, and reducing the prevalence of smoking continues to be a critical public health goal. While nicotine is the constituent primarily responsible for addiction to cigarettes, most of the harm associated with smoking comes from byproducts of tobacco combustion. Recently, two different approaches for reducing the harms of smoking have emerged, both of which focus on breaking the link between the addiction to nicotine and the harms caused by smoking. First, the addictive potential of cigarettes could be minimized by requiring a large reduction in the nicotine content of cigarettes. Evidence for a nicotine reduction policy thus far shows that the use of very low nicotine content cigarettes results in a reduction in the number of cigarettes people smoke per day and a reduction in cigarette dependence. Second, emerging alternative nicotine delivery systems (ANDS) like electronic cigarettes may provide sufficient nicotine to act as substitutes for cigarettes while delivering much lower levels of toxicants. Evidence suggests that the emergence of ANDS has increased the percentage of smokers who are able to quit. The present paper will briefly review the evidence for each of these approaches, and consider what contemporary reinforcement and addiction theories can tell us about their likely success. We argue that the most effective endgame approach is one that pursues both nicotine reduction and alternative nicotine delivery systems as complementary.